Designing A Web-Based Fish Auction Information System at TPI Tanjung Pasir Village - Hariyanto; Marini (ENCRYPTION: Journal of Information And Technology, 2023)
Internet technology is changing the way you live and how you shop in the present era. TPI (Fish Auction Place) is a market that is the center of buying and selling and auction fish. The obstacles faced by TPI include errors in the receipt / bidding of fish prices at auctions. Therefore, an auction information system is needed that is able to overcome auction transactions at TPI. This fish auction information system is built web-based with the CodeIgniter framework and MySQL database. The system development method uses a waterfall model and is tested with the blackbox testing method where the results show the running of all functional systems.